Peranan Dana Desa dalam Pengembangan Indeks Desa Membangun di Kecamatan Sibolangit Kabupaten Deli Serdang Provinsi Sumatera Utara - Beni Haryanto Tambunan; Marlon Sihombing; R Hamdani Harahap (PERSPEKTIF, 2020)
This study aims to describe the role of village funds in the development of the Village Development Index. The research method was conducted with a qualitative approach, the informants in this study were key informants, key informants and additional informants. The research location was conducted in Sibolangit sub-district with 5 sample villages, consisting of 2 disadvantaged villages, 2 developing villages, and 1 developed village. The results of this study illustrate how the village before the existence of village funds and after the existence of village funds, then the role of village funds in the development of the village index build in which in the village index builds a lot of indicators and sub-indicators of its assessment, as well as looking at factors hampering the village difficult to develop. this is a village that is still difficult to develop its area despite village funds.